2018
DOI: 10.1002/acn3.648
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation in five patients with severe disorders of consciousness

Abstract: ObjectiveThe efficacy of deep brain stimulation in disorders of consciousness remains inconclusive. We investigated bilateral 30‐Hz low‐frequency stimulation designed to overdrive neuronal activity by dual pallido‐thalamic targeting, using the Coma Recovery Scale Revised (CRS‐R) to assess conscious behavior.MethodsWe conducted a prospective, single center, observational 11‐month pilot study comprising four phases: baseline (2 months); surgery and titration (1 month); blind, random, crossover, 1.5‐month ON and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…Since 1968, a systematic review of the literature (through Medline, Embase, and web of Science) found that ten studies reporting 78 unique DoC patients who underwent DBS have been published ( Table 1 ) ( McLardy et al, 1968 ; Tsubokawa et al, 1990 ; Cohadon and Richer, 1993 ; Schiff et al, 2007 ; Yamamoto et al, 2010 ; Wojtecki et al, 2014 ; Adams et al, 2016 ; Magrassi et al, 2016 ; Chudy et al, 2018 ; Lemaire et al, 2018 ).…”
Section: Invasive Electric Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 1968, a systematic review of the literature (through Medline, Embase, and web of Science) found that ten studies reporting 78 unique DoC patients who underwent DBS have been published ( Table 1 ) ( McLardy et al, 1968 ; Tsubokawa et al, 1990 ; Cohadon and Richer, 1993 ; Schiff et al, 2007 ; Yamamoto et al, 2010 ; Wojtecki et al, 2014 ; Adams et al, 2016 ; Magrassi et al, 2016 ; Chudy et al, 2018 ; Lemaire et al, 2018 ).…”
Section: Invasive Electric Stimulationmentioning
confidence: 99%
“…Multiple targets have been tested including the reticular formation ( McLardy et al, 1968 ; Tsubokawa et al, 1990 ; Yamamoto et al, 2010 ), the central nucleus of the thalamus ( McLardy et al, 1968 ; Tsubokawa et al, 1990 ; Cohadon and Richer, 1993 ; Schiff et al, 2007 ; Yamamoto et al, 2010 ; Wojtecki et al, 2014 ; Adams et al, 2016 ; Chudy et al, 2018 ), the anterior intralaminar nuclei and paralaminar areas ( Magrassi et al, 2016 ). In two studies, pallidal stimulation was associated to thalamic targets ( Hassler et al, 1969 ; Lemaire et al, 2018 ). The multiplicity of targets in the limited number of both VS/UWS and MCS patients makes it impossible to identify the superiority of a procedure among the others.…”
Section: Invasive Electric Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this latter condition, practitioners can use the atlas like classical histological atlases from the proportional grid plates, and at the same time they can adjust or specify directly the targets from the MRI plates. Furthermore, the MDBA is of considerable value to study injured and deformed brains as indirect methods are unreliable due to the hampered landmarks in the injured brain (50). The MDBA also improves scientific knowledge of the deep brain structural aspect as revealed by current MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging results have been obtained on DoC patients with invasive electrical stimulation of the brain (16)(17)(18)(19) and recently, transcranial delivery of a low intensity electrical current over the scalp with tDCS (20)(21)(22). However, the efficacy of tDCS is debated (23)(24)(25), and its mechanisms have not been established yet.…”
Section: Main Text Introductionmentioning
confidence: 99%